(untitled) (Revista Contexto & Educação, 2026)
This article is driven by the commitment of confronting the physical and sexual violence that arise on some Brazilian children’s bodies. In contemporary times, a set of digital campaigns related to the protection of children have emerged, which produce a certain recognition of children as subjects of physical and sexual rights. Thus, we ask: How does the #NÃOSECALE campaign by the Liberta Institute operate in confronting the physical and sexual violence experienced in childhood? The analytical corpus is limited to a set of images produced by the #NÃOSECALE campaign, which are elaborated from stories of adult women, who publicly state that they were physically and sexually abused in childhood. The methodological choice is based on Schwengber (2012), considering the use of images as a methodological resource for post-critical research in education, and also, on the Foucauldian perspective (2004, 2015) about the discourse and statements conveyed in the images. The analyses allow us to recognize that the #NÃOSECALE campaign plays an educational and political role (of the word) in face of violence, which is implied in the enunciative process, that is, of exposing, producing and sharing the pain and suffering experienced in their life stories. The act of narrating oneself, telling oneself, their voices moving through this dynamic of fragility, denunciation, but of holding everyone accountable in this form of sharing. In addition, the #NÃOSECALE campaign helps many subjects to be inspired and to have the courage to talk about the violence they experience, since the stories help to break the unspeakable, making these acts of violence perceived, recognized and discussed publicly.